2020
DOI: 10.3390/molecules25122782
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Stability, and Safety Evaluation of New Polyphenolic Xanthones Towards Identification of Bioactive Compounds to Fight Skin Photoaging

Abstract: Antioxidants have long been used in the cosmetic industry to prevent skin photoaging, which is mediated by oxidative stress, making the search for new antioxidant compounds highly desirable in this field. Naturally occurring xanthones are polyphenolic compounds that can be found in microorganisms, fungi, lichens, and some higher plants. This class of polyphenols has a privileged scaffold that grants them several biological activities. We have previously identified simple oxygenated xanthones as promising antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This chemical collection of pure xanthones (>95%) was submitted to several screenings to discover their biological activities which allowed to build quantitative structure–activity relationship [(Q)SAR] models and to establish pharmacophores for antitumor [ 48 ], antioxidant [ 49 ], hepatoprotection [ 50 ], antifungal [ 29 , 51 ], antibacterial [ 52 , 53 ], antiobesity [ 54 ], antifouling [ 55 ] activities and/or targets such as monoaminoxidase (MAO) [ 56 ], P-glycoprotein (P-gp) [ 57 , 58 ], protein kinase C (PKC) [ 59 , 60 ], tyrosinase [ 61 ], over these two last decades. Moreover, from these studies several simple oxygenated ( Figure 4 ) or more complex hit compounds emerged that were additionally investigated in many directions, namely for further molecular modifications [ 62 ], for their cellular and molecular mechanism of actions [ 63 , 64 ], for their ADMET properties [ 65 , 66 , 67 ], for chromatographic applications [ 68 , 69 ] and for their incorporation in nanoformulations [ 70 , 71 ].…”
Section: A Library Of Natural Mimetic Xanthones Looking For Biologmentioning
confidence: 99%
“…This chemical collection of pure xanthones (>95%) was submitted to several screenings to discover their biological activities which allowed to build quantitative structure–activity relationship [(Q)SAR] models and to establish pharmacophores for antitumor [ 48 ], antioxidant [ 49 ], hepatoprotection [ 50 ], antifungal [ 29 , 51 ], antibacterial [ 52 , 53 ], antiobesity [ 54 ], antifouling [ 55 ] activities and/or targets such as monoaminoxidase (MAO) [ 56 ], P-glycoprotein (P-gp) [ 57 , 58 ], protein kinase C (PKC) [ 59 , 60 ], tyrosinase [ 61 ], over these two last decades. Moreover, from these studies several simple oxygenated ( Figure 4 ) or more complex hit compounds emerged that were additionally investigated in many directions, namely for further molecular modifications [ 62 ], for their cellular and molecular mechanism of actions [ 63 , 64 ], for their ADMET properties [ 65 , 66 , 67 ], for chromatographic applications [ 68 , 69 ] and for their incorporation in nanoformulations [ 70 , 71 ].…”
Section: A Library Of Natural Mimetic Xanthones Looking For Biologmentioning
confidence: 99%
“…Xanthone derivatives were studied in order to disclose their profiles as future UV filtering molecules. Resende et al (2020) reported three hydroxylated xanthone derivatives ( 162 – 164 ) with promising antioxidant activity and UV filtering characteristics [ 142 ]. Compounds 162 – 164 proved to absorb in the UVB range (280–320 nm).…”
Section: Prospectsmentioning
confidence: 99%
“…Compounds 162 – 164 proved to absorb in the UVB range (280–320 nm). Additionally, xanthone 162 showed a dual ability to protect the skin against UV damage, through DPPH scavenging action and UV-filter capacity, without phototoxicity in the HaCaT keratinocyte cell line [ 142 ]. Popiół et al (2021) also reported novel potential and innovative UV filtering compounds, combining the xanthone scaffold with €-cinnamoyl moiety [ 26 ].…”
Section: Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific requirements for selected applications or the need to fulfill quite stringent consumer needs have guided the search for new and improved sunscreens. Following this trend, Resende and coauthors report the use of new xanthones to protect the skin from photoaging [ 7 ].…”
mentioning
confidence: 99%